Pengaruh Kualitas Layanan terhadap Kepuasan Layanan (Studi pada Mahasiswa Fakultas Kedokteran Universitas Brawijaya) - Rachmania, Ika (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
Management of higher education becomes a business-like service industry which focuses on its service users. Indonesian government shifts the orientation of higher education management to service users-oriented. Therefore, student satisfaction becomes an essential aspect of higher education management. This study aims to investigate the effect of service quality on student satisfaction. The results show that the aspects of service quality simultaneously influence on student satisfaction. Partially, variables of service quality that have a significant influence on student satisfaction are access, program learning, and reputation. Therefore, Faculty of Medicine could increase student satisfaction by focusing on improving those three aspects that affect student satisfaction.